Grundtvig i Kina - Thøgersen, Stig (Grundtvig-Studier, 1995)
Grundtvig in China By Stig Thøgersen Grundtvig and the Danish folk high-schools have been known to the Chinese since the beginning of this century. From the late 1920s, the attention of Chinese reformers turned to the rural areas, and »the Danish model« subsequently came to play a major role in the Chinese political discourse as an example of a country that had reached prosperity through education, the cooperative movement, class cooperation, and agricultural development rather than through industrialization and social polarization. A major proponent of Grundtvig’s ideas was Liang Shuming who from 1931 to 1937 headed an experiment with rural reconstruction in Shandong province. Liang was a cultural conservative who advocated economic and technological progress through the establishment of rural communities centred around village schools. The article examines the sources through which Liang and other Chinese learned about Denmark and Grundtvig, and shows how the image of a Danish Utopia was created by a number of enthusiastic supporters of the folk high-school idea, among them Peter Manniche, who visited Liang in Shandong. The relative failure of Liang’s experiment is analyzed in the context of his reception of this idealized image.